Răspuns :
a^2-b^2 = (a-b)(a+b)
40=4(a+b)
a+b=10
.....................................
(x-a)(x+a)=x^2-a^2
x^2-a^2=x^2-225
scadem din ambele parti x^2 si apoi inmultim cu -1 pentru a avea + in ambele parti, atunci:
a^2=225
a=radical din 225
a=15
40=4(a+b)
a+b=10
.....................................
(x-a)(x+a)=x^2-a^2
x^2-a^2=x^2-225
scadem din ambele parti x^2 si apoi inmultim cu -1 pentru a avea + in ambele parti, atunci:
a^2=225
a=radical din 225
a=15
1).(x - a) ( x + a) = x² - a ² = x²- 225 ⇒ a² = 225 ⇒ a = √225 = 15
a = 15
Verific: ( x - 15 ) ( x + 15 ) = x² - 225
2) a²- b²=40 si a - b =4
a² - b ² = ( a - b ) ( a + b ) = 40
4 × ( a + b ) = 40
a + b = 40 : 4
a + b = 10
a = 15
Verific: ( x - 15 ) ( x + 15 ) = x² - 225
2) a²- b²=40 si a - b =4
a² - b ² = ( a - b ) ( a + b ) = 40
4 × ( a + b ) = 40
a + b = 40 : 4
a + b = 10